2016
DOI: 10.5765/jkacap.2016.27.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Characteristics of Adolescents in Monocultural and Multicultural Families in Korea

Abstract: Objectives: We aimed to compare the smoking behaviors in adolescents from monocultural and multicultural families and to evaluate the associations between their smoking behavior and number of suicide attempts. Methods: The data used in this study was collected from The Tenth Korea Youth Risk Behavior Web-based Survey. The differences in the sociodemographic characteristics between the adolescents in the multicultural and monocultural families were analyzed through the χ 2-test, and a logistic regression was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…For more lethal symptoms, such as history of suicide attempts and hospitalization after a suicide attempt, the risk is two to three times higher among MY than among nativeborn adolescents, although a similar result was not obtained for suicidal ideations/plans [10,12,19]. This suggests that despite the lack of difference in the prevalence of suicidal ideations/plans between MY and NKRY, MY are more likely to attempt suicide, which warrants special attention.…”
Section: Mental Health Among Multiethnic Youthsmentioning
confidence: 87%
See 2 more Smart Citations
“…For more lethal symptoms, such as history of suicide attempts and hospitalization after a suicide attempt, the risk is two to three times higher among MY than among nativeborn adolescents, although a similar result was not obtained for suicidal ideations/plans [10,12,19]. This suggests that despite the lack of difference in the prevalence of suicidal ideations/plans between MY and NKRY, MY are more likely to attempt suicide, which warrants special attention.…”
Section: Mental Health Among Multiethnic Youthsmentioning
confidence: 87%
“…Case-control studies that compared internalizing problems in MY, notably, depression and anxiety symptoms, with those of NKRY, showed variations in relative prevalence or severity. No significant difference was noted in reports on the prevalence and severity of internalizing symptoms including depressive and anxiety symptoms and suicidal ideation [9][10][11][12]. In other studies, however, the prevalence or severity of depressive and anxiety symptoms and suicidal behaviors among MY was high [13][14][15][16], even after adjusting for other sociodemographic variables [17,18].…”
Section: Mental Health Among Multiethnic Youthsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we consider different risk factors for suicide behavior among multicultural adolescents. First, low Korean language competence, especially in reading and writing, due to lack of mutual feedback by non-fluent parents negatively influence learning and personal relationships, and this low language competence causes stress, depression, and anxiety (16). Second, differences in outward appearance from the major population, especially in a homogenous nation like Korea, may cause bullying among kids in school, and its self-recognition can lead to poor school adjustment (16).…”
Section: Discussionmentioning
confidence: 99%
“…First, low Korean language competence, especially in reading and writing, due to lack of mutual feedback by non-fluent parents negatively influence learning and personal relationships, and this low language competence causes stress, depression, and anxiety (16). Second, differences in outward appearance from the major population, especially in a homogenous nation like Korea, may cause bullying among kids in school, and its self-recognition can lead to poor school adjustment (16). A study reported that 15.7% of teenagers with multicultural backgrounds had experienced teasing, bullying, or discrimination by their friends because of their foreign parents or for no specific reasons (17).…”
Section: Discussionmentioning
confidence: 99%